Sistem Autentikasi Hotspot Menggunakan LDAP dan Radius pada Jaringan Internet Wireless Prodi Teknik Sistem Komputer - Ahmad Herdinal Muttaqin; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Wireless network is a network utilizing radio waves that propagate openly. This network requires security to simplify the process by using user Authentication. One of technology that could be used in order to make it safer is a Lightweight Directory Access Protocol (LDAP) and Remote Authentication Dila In User Service (RADIUS). Computer Systems Engineering Department is one of the study program in the Faculty of Engineering, University of Diponegoro that reserve the internet service everyday for students need. However, internet wireless network in this department is not yet safe enough,for the necessary to secure it’s need creating a security system with LDAP and RADIUS.The results of this study is a network authentication server using OpenLDAP and FreeRadius Hotspot that will be integrated with an account of Academic Information System, which is implemented on Prodi Computer Systems Engineering Department of the University of Diponegoro.